2022
DOI: 10.1038/s41598-022-21351-9
|View full text |Cite
|
Sign up to set email alerts
|

Parametrically optimized feather degradation by Bacillus velezensis NCIM 5802 and delineation of keratin hydrolysis by multi-scale analysis for poultry waste management

Abstract: Enormous amounts of keratinaceous waste make a significant and unexploited protein reserve that can be utilized through bioconversion into high-value products using microbial keratinases. This study was intended to assess the keratinase production from a newly isolated B. velezensis NCIM 5802 that can proficiently hydrolyze chicken feathers. Incubation parameters used to produce keratinase enzyme were optimized through the Response Surface Methodology (RSM) with chicken feathers as substrate. Optimization elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…However, in acidic region not significant production was observed, this might be due to low pH value, acidic conditions may have altered ionization state of amino acid leading to decrease in activity. Most of the literatures reported maximum keratinase production in alkaline conditions due to increase in hydrolysis resulted by breakage of di-sulfide bonds and soluble proteins are liberated ( Peng et al, 2019 , Sharma et al, 2022 , Nnolim and Nwodo, 2020 ). Among the studied temperature range of 30–50 °C, a temperature of 35 °C was established to be most favorable for keratinase production (16.15 U/mL) with protein of 0.6 mg/mL ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in acidic region not significant production was observed, this might be due to low pH value, acidic conditions may have altered ionization state of amino acid leading to decrease in activity. Most of the literatures reported maximum keratinase production in alkaline conditions due to increase in hydrolysis resulted by breakage of di-sulfide bonds and soluble proteins are liberated ( Peng et al, 2019 , Sharma et al, 2022 , Nnolim and Nwodo, 2020 ). Among the studied temperature range of 30–50 °C, a temperature of 35 °C was established to be most favorable for keratinase production (16.15 U/mL) with protein of 0.6 mg/mL ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… Khalid et al, (2021) reported two industrial important enzymes; β-glucanase and protease production and optimization from Bacillus velezensis strain. A study reported feather degradation ability by Bacillus velezensis aiding in keratinase production for poultry waste management ( Sharma et al, 2022 ) Nevertheless, to the best of our understanding, very scare literatures are existing on keratinolytic Bacillus velezensis strain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations